2003
DOI: 10.1034/j.1600-079x.2003.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brain amino acids and nitric oxide after melatonin administration in rats with pentylenetetrazole‐induced seizures

Abstract: We examined the effect of melatonin on brain levels of amino acids and nitric oxide (NO) after pentylenetetrazole (PTZ)-induced seizures in rats. Animals were treated with melatonin (10-160 mg/kg, i.p.) 30 min before PTZ administration (100 mg/kg, s.c.), and were killed 3 hr later. At the dose of 80 mg/kg, melatonin significantly increased the latency (5.7-12.7 min) and decreased the duration (31.2-18.4 s) of the first seizure, reducing PTZ induced mortality from 87.5 to 25%. After kill, brains were removed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…Moreover, the anticonvulsant efficacy of agomelatine against i.v.-injected PTZ in mice was reported to involve iNOS or nNOS induction, because selective iNOS and nNOS inhibitors attenuated the effect of agomelatine (Dastgheib and Moezi, 2014). These results concurred with previous findings that the NO/L-arginine pathway was involved in the anticonvulsant effect of melatonin against clonic seizures induced by i.v.-infused PTZ (Bikjdaouene et al, 2003;YahyaviFirouz-Abadi et al, 2006). …”
Section: Melatonin and Epilepsysupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, the anticonvulsant efficacy of agomelatine against i.v.-injected PTZ in mice was reported to involve iNOS or nNOS induction, because selective iNOS and nNOS inhibitors attenuated the effect of agomelatine (Dastgheib and Moezi, 2014). These results concurred with previous findings that the NO/L-arginine pathway was involved in the anticonvulsant effect of melatonin against clonic seizures induced by i.v.-infused PTZ (Bikjdaouene et al, 2003;YahyaviFirouz-Abadi et al, 2006). …”
Section: Melatonin and Epilepsysupporting
confidence: 82%
“…Similarly with previously reported results on the anticonvulsant effects of melatonin at doses ranging from 40 to 80 mg/kg in PTZinduced seizures in a variety of species (Bikjdaouene et al, 2003;Moezi et al, 2011;Solmaz et al, 2009;Yahyavi-Firouz-Abadi et al, 2007), the authors showed that agomelatine was active at doses of 25 and 50 mg/kg. Agomelatine was also effective against pilocarpineinduced SE at a dose of 75 mg/kg (Aguiar et al, 2012), while melatonin had an anticonvulsant effect only after repeated injections in this model of epilepsy (Costa-Lotufo et al, 2002;De Lima et al, 2011).…”
Section: Melatonin and Epilepsysupporting
confidence: 63%
See 1 more Smart Citation
“…Previously, several in vivo and in vitro studies demonstrated the potential effects of theanine and melatonin in reducing oxidative stress (16,50,51). Theanine increases the production of GABA and dopamine, while it protects the cells of the hippocampus, the major center of learning and memory, from oxidative damage (17).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, melatonin modulates the electrical activity of the neurons by acting on plasma membrane receptors (Acuna-Castroviejo et al, 1995) and facilitating the GABA-ergic function (Wan et al, 1999), both of which likely contribute to anticonvulsive effects (Dawson and Encel, 1993;Golombek et al, 1996). Fifth, melatonin has been shown to inhibit brain glutamate receptors and NO production (Bikjdaouene et al, 2003;Yahyavi-Firouz-Abadi et al, 2006). The GABA-ergic effect of melatonin possibly occurs through changes in membrane ion permeability with increased chloride ion influx through GABA A -dependent chloride channels (Rosenstein et al, 1990).…”
Section: Melatonin As a Neuroprotectantmentioning
confidence: 99%